2019
DOI: 10.5812/ans.86148
|View full text |Cite
|
Sign up to set email alerts
|

Standalone Transoral Vertebroplasty for Treatment of Painful Metastatic C2 Lesion: A Case Report

Abstract: Introduction: Metastatic involvement of the spine may present with pathologic fractures, deformity, neurologic deficit due to vertebral canal compromise, and pain. Pain is usually managed with non-steroidal anti-inflammatory agents, corticosteroid injections, calcitonin, etc. Since the introduction of percutaneous vertebroplasty in 1984, it has proven as an effective armamentarium in the management of painful metastatic spine lesions. Herein, we present a case of breast cancer with osteolytic C2 metastasis, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Solitary plasmacytoma occasionally present with pathologic fractures, pain and neurological deficits secondary to canal compromise. Painful solitary plasmacytoma in any part of the vertebral column can be treated effectively by vertebroplasty [2]. PMMA injection not only can improve the cervical spine biomechanics by augmenting stiffness but also has pain relief effect due to having oncolytic properties and axial load-bearing capacity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Solitary plasmacytoma occasionally present with pathologic fractures, pain and neurological deficits secondary to canal compromise. Painful solitary plasmacytoma in any part of the vertebral column can be treated effectively by vertebroplasty [2]. PMMA injection not only can improve the cervical spine biomechanics by augmenting stiffness but also has pain relief effect due to having oncolytic properties and axial load-bearing capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Not many similar cases of this procedure are presented previously. Farrokhi et al [2] reported transoral vertebroplasty in patients with C2 metastasis for pain palliation. According to their report, this technique led to a significant rise in VAS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations